2022
DOI: 10.1101/2022.06.20.496629
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Endogenous Rab38 regulates LRRK2’s membrane recruitment and substrate Rab phosphorylation in melanocytes

Abstract: Point mutations in LRRK2 cause Parkinson's Disease and augment LRRK2's kinase activity. However, cellular pathways that enhance LRRK2 kinase function have not been identified. While overexpressed Rab29 draws LRRK2 to Golgi membranes to increase LRRK2 kinase activity, there is little evidence that endogenous Rab29 performs this function under physiological conditions. Here we identify Rab38 as a novel physiological regulator of LRRK2. In mouse melanocytes, which express high levels of Rab38, Rab32, and Rab29, k… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 51 publications
(110 reference statements)
0
1
0
Order By: Relevance
“…Rab GTPases also act upstream of LRRK2 to promote its membrane recruitment and activation (Dhekne et al, 2023; Eguchi et al, 2018; Gomez et al, 2019; Lian et al, 2023; Pfeffer, 2022; Purlyte et al, 2018; Unapanta et al, 2023; Vides et al, 2022; Wang et al, 2023a). However, although Rab GTPases promote LRRK2 kinase activity in specific contexts, recent knockout mouse studies revealed the persistence of partial or even full LRRK2 kinase activity in multiple tissues even after depletion of key Rab proteins implicated in LRRK2 activation (Dhekne et al, 2023; Kalogeropulou et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Rab GTPases also act upstream of LRRK2 to promote its membrane recruitment and activation (Dhekne et al, 2023; Eguchi et al, 2018; Gomez et al, 2019; Lian et al, 2023; Pfeffer, 2022; Purlyte et al, 2018; Unapanta et al, 2023; Vides et al, 2022; Wang et al, 2023a). However, although Rab GTPases promote LRRK2 kinase activity in specific contexts, recent knockout mouse studies revealed the persistence of partial or even full LRRK2 kinase activity in multiple tissues even after depletion of key Rab proteins implicated in LRRK2 activation (Dhekne et al, 2023; Kalogeropulou et al, 2020).…”
Section: Introductionmentioning
confidence: 99%